KARAKTERISTIK SISTEM PARLEMENTER DALAM SISTEM PEMERINTAHAN DI INDONESIA PASCA AMANDEMEN UUD 1945 - Haryani, Riastri (UNES Law Review, 2023)
Changes to the 1945 Constitution have changed the principle of people's sovereignty which was originally fully implemented by the MPR to be implemented according to the Basic Law. All state institutions in the 1945 Constitution became equal and exercised popular sovereignty within the scope of their respective authorities. Another fairly fundamental change is the shift in the power to form laws from the President to the House of Representatives (DPR), and regarding the functions and rights of the DPR institutions and the rights of DPR members. The objectives of this study are 1). To find out how the Indonesian government system is after the Amandemen of the 1945 Constitution.... 2). To find out the extent of the characteristics of the parliamentary system in the government system in Indonesia after the Amendment of the 1945 Constitution. If at first the members of the MPR had agreed that one of the changes to the 1945 Constitution was to strengthen the Presidential system, then with the changes that had occurred, it turned out that it was suspected of making an excess of power in the people's representatives. Some argue that instead of correcting the power that tends to be executive-heavy, what is created is the extreme legislative power. The format of statehood is like "sissy": The Republic is declared presidential, but the "parliamentarian" spirit is very strong. The government system of the Indonesian Presidency after the amendment of the 1945 Constitution can be interpreted as a presidential system of government with a parliamentary sense.